Keywords in Creative Writing - Bishop, Wendy (University Press of Colorado, 2006)
Wendy Bishop and David Starkey have created a remarkable resource volume for creative writing students and other writers just getting started. In two- to ten-page discussions, these authors introduce forty-one central concepts in the fields of creative writing and writing instruction, with discussions that are accessible yet grounded in scholarship and years of experience. Keywords in Creative Writing provides a brief but comprehensive introduction to the field of creative writing through its landmark terms, exploring concerns as abstract as postmodernism and identity politics alongside very practical interests of beginning writers, like contests, agents, and royalties. This approach makes the book ideal for the college classroom as well as the writer's bookshelf, and unique in the field, combining the pragmatic accessibility of popular writer's handbooks, with a wider, more scholarly vision of theory and research.